Muslim women's perspectives on designing mosque-based women's health interventions—An exploratory qualitative study. Issue 3 (16th March 2018) - Vu, Milkie; Muhammad, Hadiyah; Peek, Monica E.; Padela, Aasim I.
ABSTRACT: Mosques could serve as a promising setting for health interventions. However, little empirical data are available to guide the development of mosque-based health interventions, especially for women. We aimed to assess Muslim women's views on effective strategies for mosque-based educational interventions to promote women's health. A sample of Muslim women of diverse ethnicity and race was recruited from mosques in Chicago to participate in semi-structured interviews. In interviews, nineteen participants (aged 41–67 years) discussed characteristics of the imam and peer educator, aspects of the intervention modality, and content of health messaging that would be effective in mosque-based health programs. Participants reported that imams should have health-related knowledge to deliver to be successful, while peer educators should be respected women, educated in both religion and health. Sermons and group education classes were believed to be modalities that could reach a large portion of the community for discussions of women's health issues. Participants also suggested that sermons should use scriptural sources to convey the importance of women's health. Participants supported imam-led sermons and peer-led educational classes as effective strategies to promote women's health. Our study results speak to strategies for leveraging religious concepts to promote health among Muslim women.